Evaluating and measuring the value, use and impact of digital collections - Lorna M. Hughes (London : Facet publishing, 2012)
This edited collection authoritatively examines the current issues,themes and techniques on the use of digital collections by an international team of well respected librarians, archivists and scholars.
Includes bibliographical references and index
uaj 13/06/2014
Loans
Keywords: Digital collections